Neologisms in Modern Russian Language - Axmedjanova Olga Sergeevna (Zien Journals, 2023)
Neologisms are newly coined words or expressions that emerge in a language. In the case of the modern Russian language, neologisms often reflect changes in society, technology, and culture
Keywords: Neologisms; gender equality; masculine and feminine gender; equality